pH-Responsive Aqueous Bubbles Stabilized With Polymer Particles Carrying Poly(4-vinylpyridine) Colloidal Stabilizer - Ito, Masaya; Takano, Koki; Hanochi, Haruka; Asaumi, Yuta; Yusa, Shin-ichi; Nakamura, Yoshinobu; Fujii, Syuji (Frontiers in Chemistry, 2018)
Near-monodispersed, micrometer-sized polystyrene (PS) particles carrying pH-responsive poly(4-vinylpyridine) (P4VP) colloidal stabilizer (P4VP-PS particles) were synthesized by free radical dispersion polymerization in the presence of P4VP homopolymer and characterized in terms of diameter, diameter distribution, morphology, chemical composition, surface chemistry, and pH-response using optical and scanning electron microscopies, elemental microanalysis, X-ray photoelectron spectroscopy, laser diffraction method, and zeta potential measurement. The P4VP-PS particles can work as a pH-responsive stabilizer of aqueous bubbles by adsorption at the air-water interface. At and above pH 4.0, where the particles have partially protonated/non-protonated P4VP stabilizer with relatively hydrophobic character, particle-stabilized bubbles were formed. Optical and scanning electron microscopy studies confirmed that the P4VP-PS particles were adsorbed at the air-water interface and stabilized the aqueous bubbles. At and below pH 3.0, where the particles have cationic water-soluble P4VP stabilizer with hydrophilic character, no bubble was formed. Rapid disruption of the bubbles can be induced by lowering the solution pH; the addition of acid caused the in situ protonation of pyridine groups in P4VP, which impart water-soluble hydrophilic character to the P4VP stabilizer, and the P4VP-PS particles were desorbed from the air-water interface. The bubble stabilization/destabilization cycles could be repeated at least five times.